2013
DOI: 10.1093/gji/ggt477
|View full text |Cite
|
Sign up to set email alerts
|

Automated seismic event location by waveform coherence analysis

Abstract: Automated location of seismic events is a very important task in microseismic monitoring operations as well for local and regional seismic monitoring. Since microseismic records are generally characterized by low signal-to-noise ratio, automated location methods are requested to be noise robust and sufficiently accurate. Most of the standard automated location routines are based on the automated picking, identification and association of the first arrivals of P and S waves and on the minimization of the residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 27 publications
1
55
0
Order By: Relevance
“…Besides the imaging operator, the PWS methods also differ in preprocessing of the input waveforms and the event detection and location detection criteria. There are various CFs adopted to improve the SNR and compensate the side effects of source radiation patterns; for example, the input data are converted to envelope (Gharti et al, ; Liao et al, ; Zeng et al, ); semblance (Furumoto et al, ; W. Zhang & Zhang, ; Staněk et al, ; C. Zhang et al, ); short‐term average to long‐term average ratio (STA/LTA; Drew et al, ; Grigoli et al, ; L. Li et al, ); kurtosis (Langet et al, ; Poiata et al, ); multichannel coherency (Shi, Angus, et al, ). …”
Section: Methodologiesmentioning
confidence: 99%
“…Besides the imaging operator, the PWS methods also differ in preprocessing of the input waveforms and the event detection and location detection criteria. There are various CFs adopted to improve the SNR and compensate the side effects of source radiation patterns; for example, the input data are converted to envelope (Gharti et al, ; Liao et al, ; Zeng et al, ); semblance (Furumoto et al, ; W. Zhang & Zhang, ; Staněk et al, ; C. Zhang et al, ); short‐term average to long‐term average ratio (STA/LTA; Drew et al, ; Grigoli et al, ; L. Li et al, ); kurtosis (Langet et al, ; Poiata et al, ); multichannel coherency (Shi, Angus, et al, ). …”
Section: Methodologiesmentioning
confidence: 99%
“…‱ the energy traces (Kao & Shan, 2004, ‱ the envelope traces (Gharti et al, 2010;Liao, Kao, Rosenberger, Hsu, & Huang, 2012;Zeng et al, 2014), ‱ the STA/LTA traces (Drew et al, 2013;Grigoli et al, 2013Grigoli et al, , 2014, and ‱ the kurtosis traces (after Langet et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Langet, Maggi, Michelini, and Brenguier (2014) proposed a kurtosis based stacking function designed to work with P phases only. Alternative stacking functions have been proposed by Withers, Aster, and Young (1999), Grigoli et al (2013Grigoli et al ( , 2014 and Drew, White, Tilmann, and Tarasewicz (2013). In their approaches, they locate seismic events by stacking the short-time average to long-time average ratio (STA/LTA) traces at all stations using both P and S phases.…”
Section: Full Waveform-based Detection and Location Of Microseismicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Gajewski et al (2007) and Zhebel et al (2010) applied diffraction stacking to two-dimensional (2D) and 3D source location. Grigoli et al (2013Grigoli et al ( , 2014 used SSA to develop an imaging method by stacking STA/LTA-transformed waveforms based on traveltime. Haldorsen et al (2012Haldorsen et al ( , 2013 proposed a migration-based deconvolution method for microseismic event location and suggested that semblance-weighted (energy-weighted relevance) imaging is superior to the energy correlation imaging proposed by Artman et al (2010).…”
Section: Introductionmentioning
confidence: 99%